Akidah membawa Bencana: Membedah Dakwah Kiai Fauzan dalam Cerpen Pohon Keramat dengan Pendekatan Interdisipliner - Junaidi, Junaidi; Hakim, Imam; Hadijah, Siti; Mukhlas, Mukhlas; Mardhotillah, Nadana (MAN 4 Kota Pekanbaru, 2024)
This study aims to analyze the da’wah carried out by Kiai Fauzan in ‘Pohon Keramat’ short story by Dawam Rahardjo. Kiai Fauzan’s da’wah has an unexpected impact, reflecting the dynamics between faith, society, and the environment. This study uses text analysis methods and an interdisciplinary approach to explore the implementation of his da’wah. The results indicate that his da’wah, which adheres to absolute belief in the principles of faith (monodisciplinary), without ecological, ethical philosophy, and sociological considerations (multidisciplinary) actually causes environmental damage (nature and society). This study indicates the need for a more holistic da’wah approach, paying attention to “local wisdom” and ecological-sociological impacts so that da’wah does not only focus on changing faith, but also on environmental sustainability and social welfare. Thus, it suggests an inclusive and adaptive da’wah model, which is able to embrace society without ignoring environmental aspects that are vital to life.